Distributed Control Strategy for Automatic Power Sharing of Hybrid Energy Storage Systems with Constant Power Loads in DC Microgrids - Tian Xia; He Zhou; Bonan Huang (Mathematics, 2025)
Hybrid energy storage systems (HESSs), with superior transient response characteristics compared to conventional battery (BAT) systems, have emerged as an effective solution for power balance. However, the high penetration of constant power loads (CPLs) introduces destabilization risks to the system. To address this challenge, this paper proposes a novel hierarchical control strategy to achieve voltage stabilization and accurate current sharing. First, this paper proposes an improved P–V2 controller as the primary controller. It utilizes virtual conductance to replace the fixed coefficients of traditional droop controllers to achieve automatic power allocation between supercapacitors (SCs) and BATs, while eliminating the effects of CPLs on the voltage–current relationship. Second, based on traditional distributed control, the secondary control layer integrates a dynamic event-triggered communication mechanism, which reduces communication bandwidth requirements while maintaining precise current sharing across distributed buses. Finally, simulation and experimental results validate the effectiveness and robustness of the proposed control strategy.